INCREASING FARMERâ€™S REVENUE THROUGH THE UTILIZATION OF WATERWEEDS AS ALTERNATIVE FEED FOR TURKEY - utama, cahya setya (Seminar Nasional Pengabdian Kepada Masyarakat UNDIP 2020; Prosiding Seminar Nasional Kolaborasi Pengabdian Masyarakat UNDIP-UNNES 2019, 2020)
The specific objective expected from the community leading commodity improvement activities (PKUM) was to be able to improve the quality of turkey feed made from water weeds around partners in the form of pellet feed, a simultaneous form of a no-waste agricultural system, which can form turkey-themed villages and improve the welfare of turkey farmers in particular. The method used is a participatory rural assessment method (PRA) in which turkey breeders and the implementation team are involved together in determining the types of activities and implementation of activities in the field. Preparatory activities are joint activities between the team and the target group to determine the types of activities that the team has prepared based on the results of the initial situation analysis that will be adjusted to the actual needs and conditions. This activity was followed by counseling, training and mentoring by lecturers and mentoring teams to improve the ability of farmers to handle and present food techniques and management of agricultural waste based on conservation. Mentoring activities were carried out by the student support team (S-1) as a means to monitor and evaluate activities and as a means to improve students' skills and supplies before entering the workforce. The evaluation were carried out in stages in accordance with the stages of the work by taking into account the achievement of indicators of success at each stage. Synergy of activities between partners, universities and related â€œSKPDâ€ especially the Agriculture and Food Service was always carried out with the aim of synergizing and stabilizing activities in the field. Strengthening marketing and network groups early on was done with a community of turkey lovers who are members of the â€œSemarak Kalkunâ€ Kudus for the success of service activities. The results of this activity were obtained formulation of turkey feed based on water weed plants with composition and content that have been adapted to the needs of life and production of turkey chickens. Good response from the breeders was seen from the utilization of water-based turkey feed by looking at the delicacy and productivity of turkey in consuming weed-based feed and feed efficiency compared to factory feed with relatively similar results. Turkish breeders can save up to four thousand rupiah per kilogram of feed, so that per day the average farmer can save sixty thousand per day with an adult turkey population living 5-6 kg of 30 animals. The conclusion of this activity is the use of water weeds as turkey feed is more efficient than factory feed.